School Adjustment in Early Childhood - Rahmawati, Anayanti; Palupi, Warananingtyas; Pudyaningtyas, Adriani Rahma; Dewi, Nurul Kusuma; Sholeha, Vera; Syamsuddin, Muhammad Munif (Program Studi Magister Pendidikan Anak Usia Dini, 2026)
School adjustment is a condition that reflects the extent to which a child feels comfortable, interested, involved, and thriving in the school environment. Children need to have school adjustment since preschool because school adjustment significantly supports children's academic and social development in the future. This study aims to determine the condition of school adjustment possessed by kindergarten children. This study uses a quantitative approach with a survey method. The research sample consisted of 266 children. The sampling technique used was cluster random sampling. Data collection is based on teacher reports using the adaptation of the Short-Form Teacher Rating Scale of School Adjustment (Short-Form TRSSA). Data analysis used SPSS descriptive statistics. Result analyses show that a majority of school adjustment achievements that children can achieve are at the ability and skill level, not yet at the competence level. This condition indicates that the majority of children still need help. There are still a few children who already have the competence to do tasks independently without help. In general, there is almost no difference in school adjustment achievements between boys and girls, which means that boys and girls have a relatively similar level of mastery of school adjustment. The study's conclusion shows that most school adjustment achievements in children are not optimal. Efforts are needed to improve school adjustment because it is the foundation for children to adjust to school. When children have been able to adjust well to school, school achievement will be easier to achieve optimally.